New developments in optical coherence tomography. - Kostanyan, Tigran; Wollstein, Gadi; Schuman, Joel S (Current Opinion in Ophthalmology, 2015)
Purpose Of Review: Optical coherence tomography (OCT) has become the cornerstone technology for clinical ocular imaging in the past few years. The technology is still rapidly evolving with newly developed applications. This manuscript reviews recent innovative OCT applications for glaucoma diagnosis and management.Recent Findings: The improvements made in the technology have resulted in increased scanning speed, axial and transverse resolution, and more effective use of the OCT technology as a component of multimodal imaging tools. At the same time, the parallel evolution in novel algorithms makes it possible to efficiently analyze the increased volume of acquired data.Summary: The innovative iterations of OCT technology have the potential to further improve the performance of the technology in evaluating ocular structural and functional characteristics and longitudinal changes in glaucoma.